The effect of The Participation in Social activity Support Program on Active ageing of the Elderly in Phra nakhon si ayutthaya Province - Pongpattanapisit, Pokkrong; Koshakri, Rukchanok; Kasemsuk‎, Weha (Journal of The Royal Thai Army Nurses, 2023)
This quasi-experimental research aimed to study the effect of the participation in the social activity support program on the active ageing of the elderly in Phra Nakhon Si Ayutthaya province. The participants were 52 older adults, selected from the elderly in Phra Nakhon Si Ayutthaya province, who participated in the social activity support program with a duration of 8 weeks. The research instruments consisted of: 1) the instrument used for data collection comprising the questionnaire on general information, the assessment scale for the participation in the social activity support program of the elderly. Content validity using the CVI was 0.90 Cronbach’s coefficient was 0.86, and the assessment scale for the active ageing, Content validity using the CVI was 0.86 Cronbach’s coefficient was 0.85; 2) the instrument used in the experiment was the participation in the social activity support program. The study was conducted from September to November, 2020. The data were analyzed using descriptive statistics. The researcher compared the active ageing among the pre-participation in the social activity support program, the 4th week and 8th week of the participation in the social activity support program using Friedman test statistics. The results showed that the mean score of active ageing level was different with a statistical significance level of .05 during 8 weeks of the participation in the social activity support program. The mean scores at 4th and 8th weeks after the participation in the social activity support program were higher than that of the pre-participation with a statistically significant level of .05. However, there was no difference in the mean scores of active ageing level between 4th and 8th week with a statistically significant level of .05.